Reinterpreting Learning Preferences through Deep Learning Practices in Indonesian Senior High School English Classrooms - Ahmad Ghufran Ferdiant; Abd. Ghofur; Yunia Nabila Aziziy; KJ Vargheese (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2026)
Background: In Indonesian senior high school English classrooms, English learning is increasingly expected to involve interpretation, reflection, and sustained engagement rather than simple recall. Yet many students still use learning style labels to explain difficulty, participation, and their own sense of fit with particular tasks, despite the limited scientific support for such claims. This study explores how students draw on that language to interpret challenge and learner positioning in deep learning-oriented classrooms across culturally diverse regions of Indonesia. Methodology: Using a qualitative interpretive design, this study drew on classroom observations, in-depth interviews, and reflective learning artifacts from twenty-five purposively selected senior high school students across five Indonesian provinces representing diverse sociocultural contexts. The qualitative data were analysed through reflexive thematic analysis, with attention to both site-specific meanings and patterns across provinces. Findings: Learning style labels did not appear to represent fixed cognitive ability. Instead, students often used them to explain why certain analytical tasks felt difficult or uncomfortable Through sustained participation in scaffolded deep learning activities, many students revised earlier self-perceptions that had cast them as ‘not analytical,’ not suited’ to long texts, or weak in writing. This revision was evident when interview accounts and classroom observations showed students moving from style-based explanations of difficulty toward more flexible interpretations grounded in practice, guidance, peer interaction, and increased confidence. Differences across contexts were also visible, particularly in whether students described difficulty in terms of anxiety, restraint, dialogic support, perseverance, or intellectual challenge. Conclusion: Students’ engagement in deep learning seems to depend less on perceived learning-style fit than on how they interpret difficulty in relation to themselves as learners The findings indicate that teaching could beneficially combine cognitive support with identity-sensitive scaffolding, flexible strategy use, and the normalization of intellectual struggle. Originality: Across multiple Indonesian contexts, the originality of this study lies in reframing learning-style discourse from a presumed cognitive typology into a socially and culturally mediated interpretive resource that students use to negotiate difficulty, participation, and learner identity in deep learning contexts.